Rice Buffer Stock Maintenance Post-Rice Tariffication Law (RA11203): An Application of a Partial Equilibrium Model for Buffer Stock Level Optimization - Santos, Mary Gillian G (Animo Repository, 2024)
The Rice Tariffication Law or RA 11203 was created for the purpose of achieving food security, lowering prices at the consumer level, and making the rice industry more competitive. The opening up of the domestic rice market led to the removal of the National Food Authority’s (NFA) licensing & regulatory powers which shifted their mandate solely on maintaining an optimal level of buffer stock primarily for emergency situations. To fulfill this mandate, the NFA must anticipate and account for emergencies & uncertain events in their current operations. This paper presents an application of a Partial Equilibrium Rice Model to determine which regions NFA should purchase palay/rice to maintain the optimal level of buffer stock. Without additional imports, if a 10% disruption in palay production in region 3 was introduced, the palay reduction is 4.75% relative to the base, amounting to 27,409 MT in Semester 1 and 53,662 MT in Semester 2. In this scenario NFA had to procure palay from increases its procurement in regions 1, Region 2, Region 4b, Region 6, & Region 12 to maintain the buffer stock in Sem 2 to maintain the buffer stock at its optimal level. In the event of a disruption in production during the year, the Model can guide policy makers where to procure depending on which region will be badly hit by any type of calamity.